2019
DOI: 10.31545/aagr/102717
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of pear to bruising after harvest and storage

Abstract: S t r e s z c z e n i e. Grusza po jabłoni zajmuje drugie miejsce w światowej produkcji owoców ziarnkowych strefy klimatu umiarkowanego. W Polsce do tej pory jej produkcja była niewielka ze względu na niesprzyjające warunki klimatyczne, wrażliwość drzew i kwiatów gruszy na mrozy i przymrozki. Do poważnych problemów należy zaliczyć trudności z przechowywaniem, szybkie przejrzewanie gruszek, dużą podatność na obicia owoców podczas obrotu handlowego. O atrakcyjności gruszek decyduje nie tylko ich tekstura i barwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…The pear cvs tested differed significantly in terms of average fruit mass (Table 3). The lightest ones came from ' Alfa' trees, and the heaviest ones were from ' Amfora' trees, which was also confirmed by other researchers (Sosna, Czaplicka-Pędzich 2013;Lipa et al 2018). But the method of orchard floor management had no significant effect on this feature.…”
Section: Comparison Of Vegetative Growth Parameterssupporting
confidence: 74%
See 1 more Smart Citation
“…The pear cvs tested differed significantly in terms of average fruit mass (Table 3). The lightest ones came from ' Alfa' trees, and the heaviest ones were from ' Amfora' trees, which was also confirmed by other researchers (Sosna, Czaplicka-Pędzich 2013;Lipa et al 2018). But the method of orchard floor management had no significant effect on this feature.…”
Section: Comparison Of Vegetative Growth Parameterssupporting
confidence: 74%
“…A. capillaris application had no such effect. Pear cvs also significantly differed in terms of the concentration of soluble solids; the highest content was found in 'Dolores' pear fruit, and the lowest in ' Amfora' , which was not confirmed by Lipa et al (2018). But ' Alfa' fruits were similar in extract content as in Konopacka et al (2014).…”
Section: Comparison Of Vegetative Growth Parametersmentioning
confidence: 83%
“…Pear (Pyrus spp.) ranked second among the fruit produced and consumed in the world (Lipa et al, 2019). Pears are among the highly perishable agricultural products and have a lower storability compared to an apple, and at the same time, they are sensitive to inappropriate conditions during harvest, transport, and reloading.…”
Section: Introductionmentioning
confidence: 99%
“…ose studies demonstrated that NIR spectroscopy and hyperspectral imaging analysis is a promising technique for detecting bruise damage on fruits. However, compared with other fruits, only a few work was conducted on the pears until now and further exploration is still needed, although there have been many studies on the bruise susceptibility and storage time of pears [10,11]. Dang et al combined hyperspectral imaging with supervised classification techniques (K-nearest neighbor and support vector machine) to detect the scar area of pears [12].…”
Section: Introductionmentioning
confidence: 99%